A Genetic Structuralism Analysis of the Short Story Peradilan Rakyat by Putu Wijaya - Mardina; Muhammad Asdar; Idris; Andi Srimularahmah; Andi Tenri Sua (Edumaspul: Jurnal Pendidikan, 2026)
This study aims to analyze Putu Wijaya’s short story Peradilan Rakyat using a genetic structuralism approach. This approach is employed to examine the relationship between the intrinsic structure of the literary work and the social structure underlying its creation. The study uses a descriptive qualitative method, with Putu Wijaya’s Peradilan Rakyat as the primary data source. The research data consist of words, phrases, sentences, dialogues, narratives, and textual passages that reveal the intrinsic structure and the author’s worldview. Data were collected through intensive reading, note-taking, identification, and classification. The analysis applies the concepts of genetic structuralism, including intrinsic structure, human facts, collective subject, worldview, and the relationship between literary works and social conditions. The findings indicate that Peradilan Rakyat is constructed around the themes of justice, law, power, and social criticism. The characterization reveals conflicts between individual interests, authority, and the pursuit of justice. The setting strengthens the representation of a social environment characterized by legal problems and injustice. From the perspective of genetic structuralism, the short story is not merely an imaginative work but also represents a critical worldview concerning the practices of power and problems of justice in society. Therefore, Peradilan Rakyat can be understood as a literary work that connects individual experiences with broader social realities.